Experimental visualization of reversible magnesium storage and surface chemistry of magnesium silicide anode - Van‐Kien Hoang (Wiley-VCH, 2021)
Abstract Magnesium silicide (Mg2Si) is a new anode material candidate for Mg‐ion batteries due to the Earth‐abundance of Mg and Si and its high theoretical specific capacity of 1398 mAh/g. However, to date, no one reported its reversible Mg‐storage ability. Herein, we demonstrate for the first time the experimental visualization of a reversible electrochemical demagnesiation and magnasiation of Mg2Si film model electrode in a half‐cell with the electrolyte of PhMgCl/THF at room temperature. The Mg2+‐diffusivity, 1.3 × 10–18 cm2/s, of Mg2Si film model electrode determined with cyclic voltammetry is four orders of magnitude lower than that of Li+‐diffusivity of Mg2Si film electrode in a lithium cell, indicating a sluggish diffusion kinetics. Surface chemistry studies of the 1st discharged (demagnesiated) and the 1st cycled (re‐magnesiated) electrodes utilizing X‐ray photoelectron spectroscopy reveal that the surface of pristine Mg2Si is highly covered by various silicon oxides, and Mg2Si undergoes segregation and phase separation partly to Mg and Si along with the surface coverage of electrolyte decomposition products. Those events lower the homogeneity and connectivity of electrode composition, which limits the reaction reversibility. The data give insight into a new material design for Mg‐ion batteries.